Air-to-air fixed plate energy recovery heat exchangers for buildingâs HVAC systems - Nasif, M.S. (2019)
The provision of fresh outdoor air to buildings has become a legislated standard practice in many countries around the world to improve indoor air quality. However, in HVAC systems the cost of conditioning the outdoor air is very high. For such systems, it is essential to utilize energy recovery devices to reduce this load. Therefore, air-to-air fixed plate heat exchanger is used in buildings where the room exhaust air is passed in one stream and ambient fresh air is passed in the other stream of the heat exchanger. This heat exchanger has two types which are: sensible heat exchanger which recovers only sensible heat and enthalpy heat exchanger which utilizes membrane and recovers both sensible and latent heat (dehumidify the supplied air). This heat exchanger will precondition the fresh air prior to supplying the air to an air conditioner resulting in substantial amount of energy saving. Â© The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2019.